Judicial Discretion and Inequality in Trademark Enforcement: A Critical Study of Court-Based Recognition of Well-Known Trademarks in Pakistan - Aamir Akhtar; Umar Farooq, Advocate (`, 2026)
The protection of well-known trademarks represents a critical dimension of contemporary trademark law, particularly in jurisdictions where reputation-based rights extend beyond formal registration. In Pakistan, the recognition of well-known marks is largely dependent on judicial determination, placing significant interpretive authority in the hands of the courts. While such a court-centered model allows flexibility in addressing diverse commercial realities, it also raises concerns regarding consistency, predictability, and equality in intellectual property enforcement. This study critically examines how Pakistani courts exercise judicial discretion in determining well-known trademark status and evaluates the extent to which such discretion contributes to unequal enforcement outcomes. Adopting a qualitative doctrinal methodology, the paper analyzes the Trade Marks Ordinance 2001 alongside selected judicial decisions to identify patterns in judicial reasoning, evidentiary assessment, and procedural practice. The analysis further situates Pakistan’s approach within its international obligations under the Paris Convention and the TRIPS Agreement, while drawing comparative insights from other jurisdictions. The findings reveal significant variation in judicial approaches, particularly in relation to the weight accorded to international reputation versus domestic consumer recognition, and the evidentiary standards required to establish well-known status. These inconsistencies tend to favor multinational corporations and well-resourced litigants, who are better positioned to meet demanding evidentiary thresholds, while placing domestic enterprises at a structural disadvantage. The study argues that judicial discretion, when exercised without clear statutory guidance or institutional support, operates as a structural source of inequality rather than merely a tool of adjudication.The paper concludes that enhancing legal certainty and ensuring equitable trademark protection in Pakistan requires the development of clearer statutory criteria, proportionate evidentiary guidelines, and complementary administrative mechanisms to guide and constrain judicial discretion. https://doi.org/10.5281/zenodo.19472243